A natural product enhances apoptosis via mitochondria/caspase‐mediated pathway in HeLa cells. Issue 10 (17th May 2019) - Fan, Yangyang; Zhang, Yang; Liu, Yutian; Xu, Wenping; Yang, Yun; Hao, Youwu; Tao, Liming
Abstract: Cervical cancer is the fourth most lethal human malignancy and the leading cause of death among females around the world. Many antitumor agents have microbial origins. 5′‐ epi ‐SPA‐6952A is a new 24‐membered macrolide isolated from the cultured broth of Streptomyces diastatochromogenes . Therefore, we studied the activity and molecular mechanism of 5′‐ epi ‐SPA‐6952A in human cervical carcinoma HeLa cell. The results showed that 5′‐ epi ‐SPA‐6952A significantly inhibited cell proliferation and migration. In addition, 5′‐ epi ‐SPA‐6952A obviously increased the production of intracellular reactive oxygen species and DNA damage in HeLa cells. Moreover, nuclear shrinkage of cells, decrease in mitochondrial membrane potential, and upregulation of Bax/Bcl‐2 ratio resulted in the release of cytochrome c, and activation of caspase‐9/3 was observed in HeLa cells treated with 5′‐ epi ‐SPA‐6952A, which means it enhanced the intrinsic mitochondrial apoptosis. Besides, DNA‐damage associated proteins poly (ADP‐ribose) polymerase (PARP) and p53 were also studied, and the expressions of cleaved‐PARP and p53 were drastically increased in HeLa cells treated with 5′‐ epi ‐SPA‐6952A. Furthermore, we confirmed that 5′‐ epi‐ SPA‐6952A affected the survival of HeLa cells by blocking cell cycle progression in the G1 phase. Taken together, the results shows that 5′‐ epi ‐SPA‐6952A significantly inhibited HeLa cells proliferation via intrinsic mitochondrial apoptosis, cell cycle arrest, and blocking cell migration. Abstract : In this study, we have demonstrated that the natural product of 5′‐ epi ‐SPA‐6952A could significantly inhibit the proliferation of HeLa cells via cell cycle arrest resulting from DNA damage, and induce apoptosis of HeLa cells through the mitochondrial pathway. At the same time, we found that 5′‐ epi ‐SPA‐6952A could inhibit its migration activity significantly. Through these studies, we determined that 5′‐ epi ‐SPA‐6952A might have significant anticancer activity against HeLa cells.